Elevated 1-h post-load plasma glucose levels in normal glucose tolerance children with obesity is associated with early carotid atherosclerosis - Kılınç, Suna; Demirtaş, Tuna; Atay, Enver; Ceran, Ömer; Atay, Zeynep (Elsevier, 2020)
Context: Evidence suggests thatthe 1-h post-load plasma glucose (1-h PG) ?155 mg/dL during an oral glucose tolerance test(OGTT) predicts development oftype 2 diabetes (T2DM) and associated complications, among adults with normal glucose tolerance (NGT), but relevant data on children is scarce. Objectives: To investigate whether NGT children with obesity whose 1-h PG is ?155 mg/dL have an increased carotid intima-media thickness (IMT) and exhibit non-alcoholic fatty liver disease (NAFLD) diagnosed by ultrasonography, as compared with NGT subjects with 1-h PG <155 mg/dL and impaired glucose tolerance (IGT). Methods: Cardio-metabolic profile, OGTT, measurements of carotid IMT and liver ultrasonography were analyzed in 171 non-diabetic children with obesity. Subjects were divided into 3 groups: NGT subjects with a 1-h PG <155 mg/dL, NGT subjects with a 1-h PG ?155 mg/dL, and IGT subjects. Results: As compared with NGT individuals with a 1-h PG <155 mg/dL, NGT individuals with a 1-h PG ?155 mg/dL exhibited higher carotid IMT (0.75 ± 0.15 mm vs. 0.68 ± 0.15 mm; p < 0.05). No significant differences were observed in carotid IMT between IGT and NGT subjects with a 1-h PG ?155 mg/dL (0.75 ± 0.18 mm vs 0.75 ± 0.15 mm; p > 0.05). Of the three glycemic parameters, 1-h and 2-h PG, but not fasting glucose, were significantly correlated with carotid IMT. There were no significant differences for increased risk of having NAFLD between the three groups. Conclusions: These data suggest that a value of 1-h PG ?155 mg/dL in children and adolescents with obesity is as important as IGT with respect to cardiovascular risks.
Keywords: Obesity; 1-H Post-Load Hyperglycemia; Atherosclerosis; Non-Alcoholic Fatty Liver Disease